Efficiency Boosting by Thermal Harvesting in InGaN/GaN Light-Emitting Diodes - Lu, Shunpeng; Zhang, Yiping; Qiu, Ying; Liu, Xiao; Zhang, Menglong; Luo, Dongxiang (Frontiers in Physics, 2021)
On the same micro-LED display panel, LED pixels are always operated with high and low biased voltages simultaneously to show different brightness and colors. Thus, it is vitally important to understand the effect of the heat transmission between LEDs under high and low biased voltages. In this work, we design two different LED groups: Group A is two LEDs bonded together for heat transmission and Group B is two LEDs separated from each other. Then, the two LEDs are operated at one fixed and one tuned biased voltage respectively in each group in a vacuum chamber and the efficiency of the two groups is studied both experimentally and numerically. Here, our experimental results demonstrate that Group A exhibits a maximum improvement of 15.36% in optical output power compared with Group B. The underlying reason is that the wall-plug efficiency of the LED with a voltage lower than photon voltage (V < ℏω/q) is surprisingly enhanced by elevated temperature owing to the heat transmission by the LED under a high biased voltage in Group A. Our further study shows that in such a low voltage region the improvement in the efficiency is attributed to the enhanced carrier concentrations with elevated temperature. On the other hand, the LED in Group A under a high biased voltage further raises the overall efficiency by alleviating the thermal droop due to reduced temperature. Device temperature measurement and numerical calculation of radiative recombination under different temperatures further support the superior performance of Group A LEDs. Our research results can act as the research prototype to design the high-efficient LED arrays for better energy recycling and thermal control.